Core training and performance: a systematic review with meta-analysis - Ángela Rodríguez-Perea; Waleska Reyes-Ferrada; Daniel Jerez-Mayorga; Luis Chirosa Ríos; Roland Van den Tillar; Ignacio Chirosa Ríos; Dario Martínez-García (Termedia Publishing House, 2023)
The purposes were to synthesize as much scientific evidence as possible to determine the effect of core training on balance, throwing/hitting velocity or distance, and jumping in healthy subjects, identify the possible differences between isolated and combined core training on performance and study training and sample variables related to performance. PRISMA guidelines were followed, and a systematic search was performed in the Scopus, Web of Science, Sports Discuss, and PubMed databases with no date restrictions until November 2022. The studies were considered for this meta-analysis following PICO; a) randomized control trials and randomized allocation studies with healthy subjects and > 12 years old b)isolated or combined core training programs with a minimum of 4 weeks in length; c) athletic performance outcomes for balance, throw/hit, and jump variables should be measured; d) sufficient data to calculate effect sizes. The Cochrane Collaboration Risk of Bias Tool and the Grading of Recommendations Assessment, Development, and Evaluation approach were used for assessing methodological quality. A total of 3223 studies were identified, 22 studies were included in the systematic review and 21 for the meta-analysis. We observed that core training improved balance outcomes (ES = 1.17; p < 0.0001), throwing/hitting velocity (ES = 0.30; p = 0.14), throwing/hitting distance (ES = 3.42; p = 0.03), vertical jumping (ES = 0.69; p = 0.0003), and horizontal jump (ES = 0.84; p = 0.01). Our findings indicate that core training improved different variables of performance such as balance, throw/hit, and vertical and horizontal jump.